Study of Integrated Systems Pumps in Coast of DKI Jakarta - Boris Karlop Lubangaol; Agustinus Purna Irawan; Wati A Pranoto (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The development of DKI Jakarta is causing prone to flood threats so that required proper water management systems to reduce puddles or floods that occurred in some areas. Current water managament system is the Polder of Pluit water mangament system, and Pasar Ikan Pump system. Jakarta will plan an integrated pump system to reduce the workload of the Pluit Polder Pump System and Pasar Ikan Pump when the system is down for maintenance, the pump will be planned to include (1) Karang Pump System, (2) Haila-Marina Pump System, and (3) Sunter-Sentiong Pump System. Design: This study was conducted through three stages, collecting data, data processing, and a review of the results of the analysis. Within hydrology analysis, calculations of rainfall distribution were conducted by Normal Distribution method, Log-Normal, Gumbel, and Log Pearson III and tested using the Smirnov Kolmogorov Method. The calculation of the discharge plan using HSS Nakayasu. Hydraulic analysis with 25 years reset period of discharge plan performed using HEC-RAS software. Study of the integration of the four pump system on the north shore as a basis for drafting an alternative effort to control the puddle and flood in areas of its services and also to evaluate the discharge pump needed to improve the optimization and the pattern of the pump on the north shore system. Findings: The scenario of the operation of the four integrated pump systems provide better results than standalone scenarios, especially for the Karang Pump, Karang Ikan Pump, and Sentiong Pump with water elevation reduction of -1.67 m,-0,29 m, and 0.66 m. In contrast to Pluit Pump and Hailai-Marina Pump happen an increase in water elevation of 0.29 m and m 0.38. Worst impacts on system integration in the event of the failure of operation Pump Pluit, Hailai-Marina, and Sentiong were simultaneously or 2 pumps of the pump 3 failed to operate, so the necessary floodgates on every connecting channel between the systems. The presence of pump system Hailai-Marina and Sentiong was becoming very important, if the system pump is dead then impacted the increase of volume of the Pluit Pump of 215,0%, and 183.1% of the Pasar Ikan Pump which means Pluit Pump and Pasar Ikan Pump will work two times more weight of standalone scenarios, while the Coral Pumps operate normally without an increase in the volume of the pump i.e. 98.7%.